Curcumin suppresses inflammatory cytokines and heat shock protein 70 release and improves metabolic parameters during experimental sepsis - Letycia Silvano da Silva; Carlos Henrique Rocha Catalão; Tatiana Tocchini Felippotti; Gabriela Ravanelli de Oliveira- Pelegrin; Sérgio Petenusci; Luis Alexandre Pedro de Freitas; Maria José Alves Rocha (Taylor & Francis Group, 2017)
Context: Curcumin has been reported to have anti-inflammatory, antioxidant and hypoglycaemic properties, besides reducing mortality in sepsis. Objective: This study evaluates the biological activities of a curcumin dispersion formulated by spray-drying in experimental sepsis. Materials and methods: Male Wistar rats were subjected to sepsis by caecal ligation and puncture (CLP), controls were sham operated. The animals were treated with curcumin dispersion (100 mg/kg, p.o.) or water for 7 days prior to CLP and at 2 h after surgery. One group was used to analyze curcumin absorption through HPLC; another had the survival rate assessed during 48 h; and from a third group, blood was collected by decapitation to analyze metabolic and inflammatory parameters. Results: The plasma curcumin levels reached 2.5 ng/mL at 4 h, dropped significantly (p < 0.001) at 6 h (1.2 ng/mL), and were undetectable at 24 h in both groups. Curcumin temporarily increased the survival rate of the septic rats by 20%. Moreover, it attenuated glycaemia (p < 0.05) and volemia (p < 0.05) alterations typically observed during sepsis, and decreased the levels of the proinflammatory cytokines IL-1β and IL-6 in plasma (p < 0.001) and peritoneal lavage fluid (p < 0.05) of septic rats. Serum HSP70 levels were decreased (p < 0.01) at 24 h after CLP. Discussion and conclusion: Our results show that the curcumin dispersion dose employed was not detrimental to the septic rats. In fact, it temporarily increased their survival rate, improved important metabolic parameters, reduced proinflammatory cytokines and HSP70 production.